PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM MATERI TEKS PROSEDUR TERHADAP HASIL BELAJAR SISWA KELAS V SD - Naibaho, Hotmauli; Simbolon, Naeklan; .M, Zainuddin; Siregar, Fajar Sidik; Purnomo, Try Wahyu (Universitas Negeri Medan, 2024)
This study aims to determine the influence of the flipped classroom teaching model of procedural text material on the learning outcomes of class V of SDN 1 Turpuk Limbong. This study uses the Pre-Experimental method with one group pretest “ posttest Design. The subjects used in this study in this study are class V which totals 22 people. The tool used to collect data in this study is the results of student learning tests in the form of multiple choice as many as 25 questions. The data analysis techniques used are normality tests and hypothesis tests, namely t-tests. The results of the study showed that there was a comparison of the average pretest score of 55 and the posttest score of 81.182. Based on the results of the hypothesis test carried out with a significant Î± = 0.05, a table of 1.717 was obtained. Therefore, it can be concluded that Ha is accepted with the statement that there is an influence of the use of the Flipped classroom learning model of procedural text material on the learning outcomes of class V of SDN 1 Turpuk Limbong.